Effect of the induction of transgenerational obesity on maternal-fetal parameters - Soares, Thaigra Sousa [UNESP]; Andreolla, Ana Paula; Miranda, Carolina Abreu [UNESP]; Klöppel, Eduardo [UNESP]; Rodrigues, Luhara Silva; Moraes-Souza, Rafaianne Queiroz [UNESP]; Damasceno, Débora Cristina [UNESP]; Volpato, Gustavo Tadeu [UNESP]; Campos, Kleber Eduardo [UNESP] (Taylor & Francis, 2018)
Maternal obesity can cause complications for both women and their offspring for generations. Therefore, we intended to verify the repercussions of induction of transgenerational obesity on biochemical parameters, reproductive performance, and congenital anomaly frequency in Wistar rats. Female rats were used from successive generations. The female rats of parental generation (F0, n=10) were mated to obtain their offspring (F1 generation). F1 female rats received a monosodium glutamate (MSG) solution to induce obesity (n=07) or vehicle (control, n=06) during the neonatal period. These adult female rats were classified as normal or obese using the Lee Index, mated, and delivered offspring (F2 generation), which were also evaluated for obesity using the Lee Index in adult life (F2MSG, n=13, born from obese dams) or non-obesity status (F2Control, n=12, born from control dams), and were mated in adulthood. During pregnancy, glycemia and an oral glucose tolerance test (OGTT) were analyzed. At term pregnancy, the females were sacrificed for serum biochemical profile, maternal reproductive outcomes, and fetal development. In F2MSG rats, body weight gain at early pregnancy, glycemia by OGTT, total cholesterol, high-density-lipoprotein, and alanine transaminase activity were higher compared with those of F2Control rats. F2MSG rats also presented a lower implantation number and gravid uterus weight, increased pre-implantation loss and anomaly frequency in their fetuses (F3 generation) compared with those of F2Control rats. Therefore, even without significant changes in body weight gain, obesity was established at the end of pregnancy of Wistar rats using other biomarkers. Additionally, these rats showed multiple adverse reproductive outcomes, confirming the deleterious effects that lead to obesity.
Keywords: Fetus; obesity; rat; transgenerational